THE INFLUENCE OF BRAND CULTURE ON PURCHASING DECISIONS WITH USER GENERATED CONTENT AS A MODERATING VARIABLE - Tawil, Muhammad Risal; Setiadi, Sandi; Endarwati, Esti Tri; Octaviani, Reni Dian; Utami, Eva Yuniarti (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract This research is quantitative research with an explanatory approach, namely an approach that uses previous main references as the main source for establishing a basis for finding novelty and research gaps in the research being conducted. The data used in this research is primary data obtained from online distribution of Hyundai employees spread throughout Indonesia. The questionnaire contains statements of agree, strongly agree, normal/average, disagree, and strongly disagree from the 16 question items asked. The data was analyzed using Smart PLS 4.0. The result in this article show that the Brand Culture variable has a positive relationship and a significant influence on purchasing decisions because the P-Values value is positive and is below the 0.05 significance level, namely 0.005, which is more significant than in a number of Brand studies. Image of purchasing decisions which are at 0.012 and 0.024,. This is because the Culuter Brand can provide an icon that is clear, unique and attracts attention. Usually related to culture, the Culture Brand can reach loyal and even fanatical consumers. These results are in line with research . Apart from that, in the third row of Productivity, the third table also shows the same results if the User Generated Content variable can strengthen the influence of the Brand Culuter variable on Purchasing Decisions due to the same thing, namely the P-Values value which is positive and is below the 0.05 significance level. which is 0.000 more significant than the direct tester's 0.05. This expertise is due to the existence of User Generated Content, the dissemination of information about products can spread widely, become known to many people, and delay a number of potential consumers from making purchasing decisions. Keywords: Brand Culuter, Pruchase Decision, User Generated Content